Hopf Bifurcation Control of Subsynchronous Resonance Utilizing UPFC - Alomari, Μ. Μ.; Widyan, M. S.; Abdul-Niby, M.; Gheitasi, A. (Engineering, Technology & Applied Science Research, 2017)
The use of a unified power flow controller (UPFC) to control the bifurcations of a subsynchronous resonance (SSR) in a multi-machine power system is introduced in this study. UPFC is one of the flexible AC transmission systems (FACTS) where a voltage source converter (VSC) is used based on gate-turn-off (GTO) thyristor valve technology. Furthermore, UPFC can be used as a stabilizer by means of a power system stabilizer (PSS). The considered system is a modified version of the second system of the IEEE second benchmark model of subsynchronous resonance where the UPFC is added to its transmission line. The dynamic effects of the machine components on SSR are considered. Time domain simulations based on the complete nonlinear dynamical mathematical model are used for numerical simulations. The results in case of including UPFC are compared to the case where the transmission line is conventionally compensated (without UPFC) where two Hopf bifurcations are predicted with unstable operating point at wide range of compensation levels. For UPFC systems, it is worth to mention that the operating point of the system never loses stability at all realistic compensation degrees and therefore all power system bifurcations have been eliminated.